Residual Beta Cell Function in Newly Diagnosed Type 1 Diabetes after Treatment with Atorvastatin: The Randomized DIATOR Trial - Martin, Stephan; Herder, Christian; Schloot, Nanette C.; Koenig, Wolfgang; Heise, Tim; Heinemann, Lutz; Kolb, Hubert; on behalf of the DIATOR Study Group (PLOS ONE, 2011)
Background Recent evidence suggests that the lipid-lowering agent atorvastatin is also a potent immunomodulator. The aim of this study was to investigate the possible effect of atorvastatin on the decline of residual beta cell function in recent-onset type 1 diabetes. Methods and Findings The randomised placebo-controlled Diabetes and Atorvastatin (DIATOR) Trial included 89 patients with newly diagnosed type 1 diabetes and islet autoantibodies (mean age 30 years, 40% females), in 12 centres in Germany. Patients received placebo or 80 mg/d atorvastatin for 18 months. As primary outcome stimulated serum C-peptide levels were determined 90 min after a standardized liquid mixed meal. An intent-to-treat analysis was performed. Fasting and stimulated C-peptide levels were not significantly different between groups at 18 months. However, median fasting serum C-peptide levels dropped from baseline to 12 and 18 months in the placebo group (from 0. 34 to 0.23 and 0.20 nmol/l, p<0.001) versus a nonsignificant decline in the atorvastatin group (from 0.34 to 0.27 and 0.30 nmol/l, ns). Median stimulated C-peptide concentrations declined between baseline and 12 months (placebo from 0.89 to 0.71 nmol/l, atorvastatin from 0.88 to 0.73 nmol/l, p<0.01 each) followed by a major loss by month 18 in the placebo group (to 0.48 nmol/l, p = 0.047) but not in the atorvastatin group (to 0.71 nmol/l, ns). Median levels of total cholesterol and C-reactive protein decreased in the atorvastatin group only (p<0.001 and p = 0.04). Metabolic control was similar between groups. Conclusions Atorvastatin treatment did not significantly preserve beta cell function although there may have been a slower decline of beta-cell function which merits further study. Trial Registration ClinicalTrials.gov NCT00974740